Sleep and Sugar: Deciphering the 2003–2023 Research Landscape on Sleep Disorders and Diabetes Mellitus via Bibliometric Study - Jiang Z; Tan J; Zhou Z; Zheng H; Li Y; Wang H; Yang Q; Tian H; Chen H; Xie J; Li Z; Chen Y (Journal of Multidisciplinary Healthcare, 2025)
Ziquan Jiang,* Jianhui Tan,* Zhongming Zhou, Huihui Zheng, Yanpo Li, Haiting Wang, Qiuping Yang, Huiting Tian, Haolin Chen, Jiayi Xie, Zhiyang Li, Yexi Chen Department of Thyroid, Breast and Hernia Surgery, General Surgery, The Second Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong, 515041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yexi Chen, Department of Thyroid, Breast and Hernia Surgery, General Surgery, The Second Affiliated Hospital of Shantou University Medical College, No. 69 North Dongxia Road, Shantou, Guangdong, 515041, People’s Republic of China, Tel +8613509880123, Email yxchen3@stu.edu.cnObjective: This study aims to provide a bibliometric analysis of the research landscape on sleep disorders and diabetes mellitus, exploring the volume and impact of scholarly publications, identifying leading contributors, and discerning emerging trends and hotspots within this field.Methods: Utilizing the Web of Science™ Core Collection, we conducted a detailed search and analysis of publications related to sleep disorders and diabetes from January 2003 to December 2023. Tools like CiteSpace and VOSviewer were employed for data visualization, highlighting the contributions of authors, institutions, countries, and journals.Results: We identified 816 publications, with a notable increase in research output over time. The analysis revealed significant contributions from the USA and prominent institutions like Johns Hopkins University. Critical research hotspots include the bidirectional relationship between sleep disorders and diabetes, pathophysiological mechanisms, and the impact of targeted interventions on disease management.Conclusion: The growing body of literature underscores the complex interplay between sleep disorders and diabetes mellitus, pointing to a need for further investigation into their bidirectional relationships, underlying mechanisms, and the efficacy of interventions. This study offers a roadmap for future research, suggesting an integrated approach to understanding and managing these conditions.Keywords: bibliometric analysis, sleep disorders, diabetes, sleep quality, metabolic diseases, insulin resistance